2018
DOI: 10.5483/bmbrep.2018.51.6.025
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA: multiple players in gene expression

Abstract: Previously considered as a component of transcriptional noise, long noncoding RNAs (lncRNAs) were neglected as a therapeutic target, however, recently increasing evidence has shown that lncRNAs can participate in numerous biological processes involved in genetic regulation including epigenetic, transcriptional, and post-transcriptional regulation. In this review, we discuss the fundamental functions of lncRNAs at different regulatory levels and their roles in metabolic balance. Typical examples are introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 91 publications
1
48
0
Order By: Relevance
“…Initially, lncRNAs were considered "transcriptional noise" without any biological function [25]. Along with the increasing research investigating lncRNAs, a growing body of evidence suggests that lncRNAs play important regulatory roles in various physiological activities [26,27]. However, due to a lack of corresponding databases, current methods, such as the analysis of sequence characteristics, molecular free energy, or secondary structure, for predicting the specific functions of lncRNA genes are still imperfect, and the biological functions of the majority of lncRNAs remain vague.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, lncRNAs were considered "transcriptional noise" without any biological function [25]. Along with the increasing research investigating lncRNAs, a growing body of evidence suggests that lncRNAs play important regulatory roles in various physiological activities [26,27]. However, due to a lack of corresponding databases, current methods, such as the analysis of sequence characteristics, molecular free energy, or secondary structure, for predicting the specific functions of lncRNA genes are still imperfect, and the biological functions of the majority of lncRNAs remain vague.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are transcripts longer than 200 nucleotides, located within either the intergenic stretches or the overlapping antisense transcripts of protein coding genes. LncRNAs can regulate the expression of target genes by both transcriptional and post-transcriptional mechanisms [36]. It has been reported that LncRNAs are regulators of vascular function and their dysregulation contributes to cardiovascular diseases [37,38].…”
Section: Overview Of Epigenetic Mechanisms Of Gene Regulationmentioning
confidence: 99%
“…Furthermore, HuR is highly rich in tumor tissues, and HuR target mRNAs can encode proteins that are associated with tumorigenesis, including cell proliferation and angiogenesis . Moreover, OIP5‐AS1 can suppress cell proliferation by reducing GAK levels …”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
“…69 Moreover, OIP5-AS1 can suppress cell proliferation by reducing GAK levels. 70 In MM, downregulated OIP5-AS1 can increase the level of miR-410. 71,72 It is well known that miR-410, which acts as an oncogene or tumor suppressor, is dysregulated in cancers.…”
Section: Oip5-as1mentioning
confidence: 99%